Pengendalian Kualitas Produk Downlight dengan Implementasi Simulasi Die Casting - Trio Yonathan Teja Kusuma; Gunawan Budi Susilo; M Zulhan Iswanda (Universitas Trunojoyo Madura, 2023)
Die casting is a casting process in which molten metal is poured into a mold by injection using a piston driven by pneumatic/hydraulic energy. In some cases, the resulting product does not match the desired design because defects will occur if the configuration is not correct. There are several defects that commonly occur in the Die casting process such as cold shot, shrinkage, bubble, warping, undercut, etc. With the help of computers, these problems are expected to be reduced. Using inspire cast to visualize the injection process will facilitate the analysis of the Die casting process. With the help of this software, a better configuration can be created and implemented into the machine. However, the results are different, when simulating in the software it is said that the molten metal streams from different gates are above the recrystallization temperature of 665Â°C so it should harden and fuse better when the two molten metal streams meet. However, after implementing the new configurations into the machine, the process defects were still high at 23% for configuration 1 and 13% for configuration 2 compared to 6% for the existing configuration. However, implementing this software will reduce the cost of trial and error process to find a new configuration for a new material.